Sexually transmitted infections and HIV in self reporting men who have sex with men: A two-year study from India. Issue 5 (September 2016) - Aggarwal, Prabhav; Bhattar, Sonali; Sahani, Satyendra K.; Bhalla, Preena; Garg, Vijay K.
Summary: Homosexuality is not legally and socially accepted in India. Thus, this area of research has largely been ignored by Indian authors, resulting in dearth of knowledge, particularly with respect to sexually transmitted infections (STIs) in this high-risk group. Over a period of two years (2013–2014), 738 males sought care at skin and venereal diseases clinics, 52 (7.05%, 95% CI = 5.4–9.14%) of who identified themselves as MSM and were enrolled in the study. Diagnosis was made on the basis of clinical presentation and laboratory testing, wherever indicated. Thirty six percent of MSM had only homosexual preferences, while 64% were bisexual. The most common sexually transmitted infection was genital warts (23.08%, 95% CI = 13.58–36.28%). Fourteen patients (26.92%, 95% CI = 16.67–40.35%) were VDRL and TPHA positive (two, five and four with primary syphilis, secondary syphilis and latent syphilis, respectively). These were followed by genital herpes (11.54%, 95% CI = 5.03–23.34%), genital molluscum contagiosum (9.62% 95% CI = 3.75–21.04%), and gonorrhea (5.77%, 95% CI = 1.38–16.25%). Of those tested, 23.08% (95% CI = 13.58–36.28%) of patients were reactive for HIV serology. Thus, MSM is a high-risk group with high prevalence of HIV and other STIs in this group, mandating greater focus, education and counseling.